2019
DOI: 10.1111/ans.15357
|View full text |Cite
|
Sign up to set email alerts
|

Distal intestinal obstruction syndrome: an important differential diagnosis for abdominal pain in patients with cystic fibrosis

Abstract: As life expectancy for those with cystic fibrosis (CF) now exceeds 40 years of age, adult hospitals away from specialized CF services are being exposed more frequently to people with acute complications of CF. Well-known manifestations of CF include pulmonary disease and pancreatic insufficiency with malabsorption. However, a less well-known entity is distal intestinal obstruction syndrome (DIOS), which is an important cause of obstructive symptoms in people with CF that must be differentiated from other cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Intestinal obstruction is an obstacle to the passage of intestinal contents caused by various reasons, which leads to clinical symptoms such as abdominal pain, constipation, vomiting, absence of defecation, and exhaustion in patients, and even results in systemic physiological disorders and endangers life safety [1]. Acute intestinal obstruction (AIO) is an extremely common type of intestinal obstruction, which has the characteristics of rapid onset, complex signs, and changeable causes [2]. Previous data revealed that AIO patients are unable to eat due to frequent vomiting, which can rapidly lead to decreased blood volume and hemoconcentration, and even endanger the life of patients when it is serious [3].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal obstruction is an obstacle to the passage of intestinal contents caused by various reasons, which leads to clinical symptoms such as abdominal pain, constipation, vomiting, absence of defecation, and exhaustion in patients, and even results in systemic physiological disorders and endangers life safety [1]. Acute intestinal obstruction (AIO) is an extremely common type of intestinal obstruction, which has the characteristics of rapid onset, complex signs, and changeable causes [2]. Previous data revealed that AIO patients are unable to eat due to frequent vomiting, which can rapidly lead to decreased blood volume and hemoconcentration, and even endanger the life of patients when it is serious [3].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of function of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel causes varied physiological malfunctions including chronic lung inflammation 1 , CF-related diabetes 2 , impaired growth and weight 3 , 4 and obstructive bowel disease 5 all contributing to a disease that is difficult to manage. While advances in health care have prolonged lifespan, stresses related to early mortality, repeated hospitalization and management of a chronic disease contributes to poor mental health in CF patients including depression and anxiety 6 10 .…”
Section: Introductionmentioning
confidence: 99%
“…CT scan of the abdomen demonstrates proximal small bowel dilatation with inspissated fecal material in the bowel. 9 Appendicitis, appendicular mucocele or complete occlusion must be ruled out. The treatment of PIOS is above all empirical in the absence of controlled and randomized studies.…”
Section: Case Reportmentioning
confidence: 99%